2015
DOI: 10.1055/s-0035-1564448
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Polyglycolic Acid Sheet Covering and Platelet-Rich Plasma after Video-Assisted Thoracic Surgery for Spontaneous Pneumothorax

Abstract: Video-assisted thoracic surgery (VATS) is widely used for the treatment of spontaneous pneumothorax, and the recurrence rate is high. The goal of the study was to examine the use of polyglycolic acid (PGA) sheets, together with platelet-rich plasma (PRP) from autologous blood for the prevention of postoperative recurrence of spontaneous pneumothorax. We performed a retrospective study of 65 patients who underwent VATS for spontaneous pneumothorax from March 2008 to November 2011. The patients were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The first reason is that a PGA patch can decrease the rate of postoperative pulmonary fistula in the pleura. Second, a PGA patch can avoid new bullous formation and inhibit rupture of new bullae [13,23,24]. Our results showed that the incidence of postoperative recurrence is greater in the non-PGA group than in the PGA group; Considering the difference between primary spontaneous pneumothorax and secondary spontaneous pneumothorax, we conducted a subgroup analysis of two spontaneous pneumothoraxes, the results showed that PGA was equally effective in reducing the recurrence of pneumothorax.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The first reason is that a PGA patch can decrease the rate of postoperative pulmonary fistula in the pleura. Second, a PGA patch can avoid new bullous formation and inhibit rupture of new bullae [13,23,24]. Our results showed that the incidence of postoperative recurrence is greater in the non-PGA group than in the PGA group; Considering the difference between primary spontaneous pneumothorax and secondary spontaneous pneumothorax, we conducted a subgroup analysis of two spontaneous pneumothoraxes, the results showed that PGA was equally effective in reducing the recurrence of pneumothorax.…”
Section: Discussionmentioning
confidence: 72%
“…Video-assisted thoracoscopic bullectomy has been a main treatment of spontaneous pneumothorax; however, according to the past several studies, the rate of recurrence is high, ranging from 9.4 to 24.5% [1,3,13,14]. Although postoperative pneumothorax is not lifethreatening, it can interfere greatly with patients' quality of life, so it is important to decrease its rate of recurrence [4,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation